Analysis of mixing construction and demolition waste with soil for embankments - Arruda, Mauro Sergio Zakia Jabur [UNESP]; Mancini, Sandro Donnini [UNESP]; Rodrigues, Roger Augusto [UNESP]; Antunes, Maria Lucia Pereira [UNESP] (Ice Publishing, 2022)
In some countries, there are cases of inadequate destination and even final disposal of construction and demolition waste (CDW), which contributes to environmental degradation and material wastes. The construction sector is a great consumer of natural resources, and CDW can sometimes be useful to minimise the need for natural materials, including embankment filling, which could use a large volume of material. In these cases, the use of CDW can be promising if the embankment quality is not affected; and it will have a great economic advantage. This paper aims to assess experimentally the feasibility and potential benefits of employing CDW mixed with soil in embankments. CDW samples were collected from three recycling facilities in Brazil and mixed with lateritic soil. Compaction tests determined optimum parameters of the lateritic soil, and the soil mixed with 25 and 50% of CDW. The maximum dry densities of the mixtures changed slightly compared to natural soil. The mixtures' optimum water content increased only 2% in relation to the soil without waste, which means that the compaction of the mixtures will require 10-20% more water, depending on CDW quality. Results show that these materials and proportions can be considered for possible application in embankments.
Keywords: Compaction; Strength & testing of materials; Waste valorisation; UN SDG 11: Sustainable cities and communities